Diadenosine pentaphosphate modulates glomerular arteriolar tone and glomerular filtration rate. (3rd December 2014) - Patzak, A.; Carlström, M.; Sendeski, M. M.; Lai, E. Y.; Liu, Z. Z.; Sällström, J.; Flöge, J.; Heintz, B.; Jankowski, J.; Jankowski, V.
Abstract Introduction Mechanisms and participating substances involved in the reduction of glomerular filtration (GFR) in contrast‐induced acute kidney injury (CI‐AKI) are still matter of debate. We hypothesized that diadenosine polyphosphates are released by the action of contrast media on tubular cells and may act on glomerular arterioles and reduce GFR. Methods Freshly isolated rat tubules were treated with the contrast medium iodixanol (47 mg iodine per mL) at 37 °C for 20 min. The content of ApnA (n = 3–6) in the supernatant of treated tubules and in the plasma of healthy persons and patients with AKI was analysed using reversed‐phase chromatography, affinity chromatography and mass spectrometry. GFR was obtained in conscious mice by inulin clearance. Concentration response curves for ApnA (n = 3–6, 10−12–10−5 mol L−1) were measured in isolated perfused glomerular arterioles. Results Iodixanol treatment of tubules significantly increased the concentration of ApnA (n = 3–5) in the supernatant. Ap6A was below the detection limit. AKI patient shows higher concentrations of ApnA compared to healthy. Application of Ap5A significantly reduced the GFR in conscious mice. Ap5A reduced afferent arteriolar diameters, but did not influence efferent arterioles. The constrictor effect on afferent arterioles was strong immediately after application, but weakened with time. Then, non‐selective P2 inhibitor suramin blocked the Ap5A‐induced constriction. Conclusion The data suggest that Ap5A plays a role in the pathophysiology of CI‐AKI. We show a contrast media‐induced release of Ap5A from tubules, which might increase afferent arteriolar resistance and reduce the GFR.